Breast Cancer: Overview of Modern Management - Uddin, Dayem; Hannan, ABM Abdul; Begum, Khodeja Nahar (TAJ: Journal of Teachers Association, 2009)
Potential benefits of local and or systemic therapy of breast cancer depending on the patient's stage. Local therapy would be expected to be most effective at a time when the patient's disease is confined within the ducts or lobules (premalignant or noninvasive) or is only minimally invasive. Local therapy would be expected to have little if any effect in patients with widespread systemic disease (macrometastatic), except in specific cases of isolated organ sites requiring palliation. Systemic therapy would be expected to have its greatest effect in prolonging survival in patients who are most likely to have distant metastases but whose disease has not had an opportunity to develop substantial resistance (micrometastatic), which might develop with ongoing tumor growth. However, tamoxifen may serve to suppers emergence of new primary cancer, and chest wall and surrounding lymph node radiation may prevent may prevent subsequent micrometastases. doi: 10.3329/taj.v18i2.3197 TAJ 2005; 18(2): 140-143